Treatment of Retained Placenta in Cows - Shavkat Baliev; Jamshid Ochilov (Global Scientific Publishing, 2023)
This article describes the effectiveness of uterotonic, oxytocin, and iodopen drugs in the treatment of infertility caused by placental retention and shortening the service period in productive cows cared for on farms today.
Keywords: Cow; placenta; endometritis; involution